Association of rs1059004 polymorphism in the OLIG2 locus with functional brain network in first-episode negative schizophrenia. (30th September 2020) - Lv, Yahui; Wu, Sijia; Lin, Yanyan; Wang, Xuwen; Wang, Jijun; Cai, Suping; Huang, Liyu
Highlights: SZ patients carrying risk a allele have reduced functional connectivity strength;. All groups show small-world properties regardless of the genotype;. The PCUN.R and mTPO.L of SZ patients between different genotypes have significant difference in efficiency;. There are correlation among functional connectivity, functional network and behavioral performances in SZ patients. Abstract: Schizophrenia has often been viewed as a disorder of connectivity. The single nucleotide polymorphism rs1059004 in the oligodendrocyte lineage transcription factor 2 gene locus has been reported to be associated with schizophrenia. We measured the functional connectivity and functional brain network topology properties in 49 schizophrenic patients and 47 healthy controls. We compared the strength and diversity of the functional connectivity and topological properties of functional networks between different genotypes. The correlations among functional connectivity, topological properties and behavioral performances were also investigated in this study. We found that the connectivity strength of schizophrenic patients carrying the risk A allele was generally decreased whereas connectivity diversity was increased. Regarding topological properties, all groups showed small-world properties, the nodal efficiency showed significant differences in the right precuneus and left middle temporal pole between different genotypes in schizophrenic patients. Moreover, the nodal efficiency in the left middle temporal pole was positively correlated with the neuropsychological assessment battery results of the schizophrenic patients who were homozygous for the C allele. Our results elucidate the contribution of rs1059004 to the functional brain network, and may help enhance the present understanding of the role of risk gene in the functional dysconnectivity of schizophrenia.